AMINOLYSIS OF Z-4-FURYLIDENE OXAZOLIN-5-ONE DERIVATIVES-CONFIGURATION AND KINETICS - Abdelrehim, El-sayed M.; Abd Elatif, Mohammed (European Scientific Journal, ESJ, 2014)
The kinetics of ring opening of (Z)-4-(substitutedarylidene)-2-aryloxazolin-5-ones 1a-e with piperidine in acetonirile has been investigated in the temperature range (25-500C) which were found to be a second-order reaction, the estimated positive ρ values, thermodynamic parameters and reaction rate constants are consisting with the suggested a stepwise mechanism, where the first stage is a slow perpendicular nucleophilic attack of piperidine on carbonyl group forming the intermediate (T#) passing through a cyclic zwitterionic transition state followed by expelling of the leaving group. As well as the products of the reaction 3a-e will be identified and determined their configuration assignments which based on NMR analysis, applying the 1H-NMR additivy increment rules and the gated decoupling technique 13C-NMR (3JCH) which indicates that the compounds 3a-e, exclusively have the Zconfiguration.